2019
DOI: 10.1093/mmy/myz033
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Candida auris on latex and nitrile gloves with transmission to sterile urinary catheters‡

Abstract: Candida auris’ ability to persist on contaminated gloves and transmit to urinary catheters was evaluated. 105 and 103 cfu/ml suspensions of eight Candida species including C. auris were inoculated on latex and nitrile gloves fingertips and touched on agar surface at different time intervals. Urinary catheter piece, touched by latex glove carrying Candida spp. suspensions at various time intervals, was cultured by roll-plate method. C.auris persisted on latex gloves at both 105 and 103 cfu/ml up to 3 minutes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In this study, it was possible to determine that the persistence of C. auris in latex gloves is 624 h equivalent to 26 days without control of physical parameters; This finding contrasts with other studies in which they report the persistence of up to 14 days of C. auris on plastic surfaces under conditions of temperature and controlled humidity8; It has also been shown that C. auris survives on a variety of surface types, including dry, wet and plastic surfaces, indicating the potential for environmental contamination that this microorganism can develop 16 Persistence is attributed to stress tolerance levels, high temperatures 17 and biofilm formation 18,19 however this study cannot be attributed the ability to persist the formation of biofilms since they were not studied, but at levels of tolerance to stress due to nutrient shortages. 22 . In this study, the persistence of C. auris, C. parapsilosis and S. cerevisiae on surfaces of latex gloves and disposable gown was evaluated; it was determined that the physical and chemical characteristics may or may not allow colonization by microorganisms; in the area of health, it is sought that most medical devices are for sterile use; however, the spread of microorganisms depends on the use and composition of the implement; in the case of latex gloves the microorganisms used were less persistent than in the disposable gown, one of the possibilities is the porosity of the two surfaces, the gloves have less porosity compared to the gown, at the time the inoculum is added (suspension), the surface of the glove does not absorb but keeps the inoculum on it, contrary to the gown who does absorb the added inoculum, this is due to the composition of the implement.…”
Section: Persistence Of Candida Auris In Disposablementioning
confidence: 99%
“…In this study, it was possible to determine that the persistence of C. auris in latex gloves is 624 h equivalent to 26 days without control of physical parameters; This finding contrasts with other studies in which they report the persistence of up to 14 days of C. auris on plastic surfaces under conditions of temperature and controlled humidity8; It has also been shown that C. auris survives on a variety of surface types, including dry, wet and plastic surfaces, indicating the potential for environmental contamination that this microorganism can develop 16 Persistence is attributed to stress tolerance levels, high temperatures 17 and biofilm formation 18,19 however this study cannot be attributed the ability to persist the formation of biofilms since they were not studied, but at levels of tolerance to stress due to nutrient shortages. 22 . In this study, the persistence of C. auris, C. parapsilosis and S. cerevisiae on surfaces of latex gloves and disposable gown was evaluated; it was determined that the physical and chemical characteristics may or may not allow colonization by microorganisms; in the area of health, it is sought that most medical devices are for sterile use; however, the spread of microorganisms depends on the use and composition of the implement; in the case of latex gloves the microorganisms used were less persistent than in the disposable gown, one of the possibilities is the porosity of the two surfaces, the gloves have less porosity compared to the gown, at the time the inoculum is added (suspension), the surface of the glove does not absorb but keeps the inoculum on it, contrary to the gown who does absorb the added inoculum, this is due to the composition of the implement.…”
Section: Persistence Of Candida Auris In Disposablementioning
confidence: 99%
“…The colonization of surfaces in patients undergoing any type of instrumentalisation increases, on the one hand, the risk of invasive candidiasis and generating new outbreaks, and decreases, on the other hand, the possibility of eradicating patient colonisation. A large number of IFI cases due to C. auris have been described related to health devices, such as urinary tract infections (UTI) in patients with indwelling catheters, cardiovascular infections, or neurosurgical instrument-related infections [ 16 , 17 , 18 , 114 , 115 ]. The C. auris tendency to form biofilms in human skin as well as in animal skin models with an elevated microbiological burden [ 116 ] has been related to an increased expression of adhesins ( IFF4 , CSA1 , PGA26 , PGA52 , PGA7 , HYR3 , and ALS5 ) [ 117 ], with differential regulation based on the biofilm maturity [ 117 , 118 ].…”
Section: Microbiological Features Of C Aurismentioning
confidence: 99%
“…Biofilms are structured microbial communities that form on abiotic and biotic surfaces and are embedded in an extracellular matrix influencing drug resistance by hindering drug penetration into dense biofilms. A large number of C. auris infections has been connected to the use of health devices that can serve as a source of infection and can spread to other parts of the body ( Eyre et al, 2018 ; Ruiz-Gaitán et al, 2018 ; Castro et al, 2019 ; Jabeen et al, 2020 ). According to these characteristics, C. auris is an emerging invasive pathogen in critically ill COVID-19 patients that requires the implementation of strict infectious control measures such as contact precautions, screening, and diligent decolonization of the patients to prevent the potential nosocomial spread.…”
Section: Introductionmentioning
confidence: 99%